2001
DOI: 10.1111/j.1574-6968.2001.tb10892.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux response to phosphoglucose isomerase knock-out in Escherichia coli and impact of overexpression of the soluble transhydrogenase UdhA

Abstract: Blocking glycolytic breakdown of glucose by inactivation of phosphoglucose isomerase (Pgi) in Escherichia coli led to a greatly reduced maximum specific growth rate. Examination of the operational catabolic pathways and their flux ratios using [U-(13)C(6)]glucose-labeling experiments and metabolic flux ratio analysis provide evidence for the pentose phosphate (PP) pathway as the primary route of glucose catabolism in the knock-out mutant. The resulting extensive flux through the PP pathway disturbs apparently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
138
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(151 citation statements)
references
References 18 publications
10
138
1
Order By: Relevance
“…An additional factor in the redox-balancing capacity of E. coli is the presence of two kinds of transhydrogenases (Fuhrer & Sauer, 2009;Sauer et al, 2004). For example, it was observed that the overexpression of the transhydrogenase UdhA helps to dissipate the NADPH imbalance in the Dpgi mutant, increasing the growth rate of this mutant strain (Canonaco et al, 2001). Given the balancing capacity provided by the transhydrogenases, it is not clear why the dehydrogenases in the oxPPP from E. coli have evolved to be specific for NADP.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An additional factor in the redox-balancing capacity of E. coli is the presence of two kinds of transhydrogenases (Fuhrer & Sauer, 2009;Sauer et al, 2004). For example, it was observed that the overexpression of the transhydrogenase UdhA helps to dissipate the NADPH imbalance in the Dpgi mutant, increasing the growth rate of this mutant strain (Canonaco et al, 2001). Given the balancing capacity provided by the transhydrogenases, it is not clear why the dehydrogenases in the oxPPP from E. coli have evolved to be specific for NADP.…”
Section: Introductionmentioning
confidence: 99%
“…When these strains were grown aerobically with glucose as the sole carbon source, the mutant Dpgi-NAD-G6PDH showed a growth rate 59 % faster than that observed for the parental Dpgi (Table 2). Canonaco et al (2001) demonstrated that the impaired growth rate of the Dpgi strain is caused by the relative excess of NADPH produced when almost the entire assimilated glucose flows through the oxPPP. The results shown here are consistent with the results of Canonaco et al (2001) because the substitution of an NADPH-producing enzyme by an NADH-producing enzyme would partially relieve the relative excess of NADPH observed in Dpgi, improving its growth rate.…”
Section: Design and Kinetic Study Of An Nad-preferring G6pdhmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of respiratory growth due to excess NADPH accumulation has been documented in yeast (Boles et al 1993;Fiaux et al 2003;Nissen et al, 2001) and in a strain of E. coli lacking the cytoplasmic transhydrogenase UdhA (Sauer et al, 2004). UdhA catalyses the oxidation of NADPH, with NAD serving as the electron acceptor, and is essential for growth of E. coli under two conditions in which the rate of NADPH production exceeds its consumption: growth on glucose in the absence of the phosphoglucose isomerase and growth in minimal medium containing acetate as the sole electron donor and carbon source (Canonaco et al, 2001;Sauer et al, 2004). Thus, one possible explanation for the phenotype of the SfrAB-null strain is that SfrAB serves as a major route for NADP regeneration in G. sulfurreducens.…”
Section: Fe(iii) Reduction By Spheroplastsmentioning
confidence: 99%
“…3 corresponds to the interconversion of NADPH and NADH catalysed by the soluble and membrane-bound transhydrogenases SthA and PntAB, respectively (Sauer et al, 2004;Canonaco et al, 2001). This flux is positive in MG1655 and in Pfl2, implying that the reduced cofactor NADH is converted to the biosynthetic reducing power NADPH.…”
Section: Resultsmentioning
confidence: 99%